Development of bioinformatics methods and platforms to characterize chromatin interactions - Chen, Kaijing (Nanyang Technological University, 2024)
Chromatin interactions are loops between genomic elements, such as enhancers and promoters, that regulate gene transcription. High throughput chromosome conformation capture (Hi-C) is an important method for studying chromatin interactions in the whole genome. Our aim is to understand or address the challenges and gaps identified in analyzing Hi-C sequencing data and develop innovative solutions to enhance our understanding of the alterations of chromatin interactions in the context of cancer. In the first project, we defined a super-silencer as a genomic region of high H3K27me3 signal comprised of multiple silencers that can work as a single entity to repress the transcription of genes that are important to the regulation of cell identity. Then we asked about the possibility of using drug treatments that affect oncogenes regulated by super-silencers as potential therapies for cancer. Our hypothesis was that the combinatorial treatment of EZH2 inhibitor GlaxoSmithKline 343 (GSK343) and REST inhibitor X5050 ("GR treatment") could upregulate apoptotic genes regulated by "super-silencers" and disrupt chromatin interactions of oncogenes, thus giving rise to antitumor effects. We found that the GR treatment resulted in a significant loss of chromatin interaction. Furthermore, certain apoptotic genes such as CDKN1A, which are regulated by super-silencers through chromatin interactions, showed increased expression levels. It is important to note that a lot of cell death was also observed during the GR treatment. In conclusion, we revealed the underlying mechanism of GR treatment in cell death, which has the potential to lead to cancer ablation through the initiation of apoptosis and disrupt "super-silencer"-related oncogenes regulated by chromatin interactions. This combinatorial treatment offers a promising therapeutic avenue for myeloid leukemias. To address the limitations in current Hi-C sequencing analysis approaches and to identify additional factors influencing chromatin architecture beyond super-silencers, we also built two pipelines: "SIQHiC-box" for detecting global changes in chromatin contact frequency and "iChIAP" for obtaining chromatin interaction data and critical genomic features from the same Hi-C sequencing data. Taken together, our work presents a new perspective on super-silencers and their relationship with chromatin interactions. Additionally, we have developed two new pipelines to facilitate the comprehension of alterations in chromatin interactions in cells. In the future, we hope these pipelines will be useful in uncovering more characteristics of super-silencers or factors related to chromatin interactions and identifying more characteristics of chromatin interactions that contribute to cancer progression.